COPUS, PORTAAL, or DART? Classroom Observation Tool Comparison From the Instructor User’s Perspective - Asgari, Mitra; Miles, Asha M.; Lisboa, Maria Sol; Sarvary, Mark A. (Frontiers in Education, 2021)
Classroom observation tools are used to evaluate teaching and learning activities, and to provide constructive feedback to instructors. To help instructors with selecting a suitable tool based on their needs and available resources, in this study, a group of observers assessed lectures of an introductory biology course using three, broadly cited classroom assessment tools in the STEM field: the Classroom Observation Protocol for Undergraduate STEM (COPUS); the Practical Observation Rubric to Assess Active Learning (PORTAAL); and the Decibel Analysis for Research in Teaching (DART). From a user’s perspective, we evaluated 1) the type and extent of information each tool provides, and 2) the time investment and difficulty of working with each tool. The assessment result of each tool was compared, with a list of expected outcomes generated by surveying a group of college instructors and with the result of a self-teaching assessment tool, Teaching Practices Inventory (TPI). Our findings conclude that each tool provided valuable assessment with a broad range of outcomes and time investment: PORTAAL offered the most detailed information on the quality of teaching practices and students’ engagement, but it demanded the greatest time investment. DART provided a basic estimation of active learning proportion with the least effort. The level of assessment outcome and the time investment when using COPUS was found to be less than PORTAAL, and more than DART. The TPI self-assessment outcome was found to be slightly optimistic regarding the proportion of active learning practices used in the studied course. This comparative study can help instructors in selecting a tool that suits their needs and available resources for a better assessment of their classroom teaching and learning.